Ouvrages rustiques et ornements : la technique de la rocaille et ses artisans dans les jardins et parcs urbains du Brésil au tournant du XXe siècle - Cristiane Maria Magalhães (Brésil(s), 2017)
This article deals with the proliferation of rocailleurs and cascateiros and their works, the rocailles, in the southeast of Brazil. These adornments were made from reinforced concrete between the end of the nineteenth century and the first two decades of the twentieth century, for gardens and parks in the landscaped paysager style. The repertoire of rocaille works included bridges, fountain borders, ponds, waterfalls and artificial caves, viewpoints, bandstands, benches, kiosks, tables and arbors. These artifacts were mostly made to mimic the textures of tree trunks, bamboos, vines, the shape of rocky clumps and small insects, among other organic and mineral elements. The highpoint of these reinforced concrete embellishments for gardens, public parks, and the homes of wealthy families in the urban centers and also in farms occurred between 1870 and the 1920s. During that time, advertisements in newspapers, notably those in Rio de Janeiro, announced the services of gardeners, rocailleurs, and cascateiros, specialists in the art and technique of building waterfalls, caves, and other fashionable works in reinforced concrete. This essay examines the work of foreigners like the French chef rocailleur Paul Villon and the Portuguese cascateiro Francisco da Silva, taken as examples of a historical process that had its beginning, apogee, and decline during the aforementioned period.